Evaluation of Adverse Drug Reaction Reporting on the Badan POM Website in Yogyakarta Special Region - Ernawati, Hafifah; Ikawati, Zullies; Puspitasari, Ika; Abdoellah, Siti Asfijah; Kurniawati, Fivy (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Adverse Drug Reaction (ADR) is defined as a harmful and unintended response to a drug, as a part of the pharmacovigilance system to identify drug safety-related issues. As a regulatory, the Indonesian Food and Drug Authority (BPOM) has facilitated an online reporting platform for healthcare professionals via the website www.e-meso.pom.go.id.Objectives: The objective of this study is to characterize Adverse Drug Reaction (ADR) reporting within the Special Region of Yogyakarta, serving as an early detection mechanism for potential drug safety hazards.Methods: This observational cross-sectional survey study utilized ADR reporting data obtained from the MESO website of the Indonesian Food and Drug Authority in the Special Region of Yogyakarta (DIY). The collected data were subjected to descriptive analysis. A total of 169 reports were analyzed, encompassing 255 suspected drugs and 255 ADR events.Results: The report identifies three predominant groups of patient disease characteristics: diseases of the circulatory system (15.38%), certain infectious and parasitic diseases (11.24%), and diseases of the respiratory system (9.47%). Regarding the type of ADR based on its Sub Organ Class (SOC), Skin and subcutaneous tissue disorders is most frequently involved (21.57%). The antibiotic group is the most commonly suspected type of drug (34.90%), with Levofloxacin and Ceftriaxone being the most implicated in causing ADR (11.24%). Oral administration is the most common route associated with ADR, followed by intravenous administration.Conclusion: In 2023, the monitoring of ADR in the Special Region of Yogyakarta revealed that antibiotics were the most frequently suspected drug class in relation to ADR. The dermatological organ system was also identified as the predominant organ affected by these reactions.